La morale des libres penseurs prolétariens : entre dénonciation de la pédophilie du clergé et promotion d’une approche alternative de la sexualité (France, années 1920-1930) - Laura Pettinaroli (Cahiers d’histoire.)
Associated with the communist movement from the beginning of the 1920s, the French proletarian freethinkers (Libre pensée d'action sociale 1921-1924, libre pensée révolutionnaire 1926-1932, Association des travailleurs sans dieu 1933-1936) anchored their anti-religious critique in the class struggle. They also regularly emphasized sexual issues from different angles, ranging from vigorous denunciation of clerical pedophilia to defense of neo-Malthusianism, feminism, and the Soviet achievements on divorce and abortion legislation. This article, focusing on the printed sources of the proletarian freethinkers, illustrates a little-known aspect of these cultural organizations linked to the communist movement, thus opening perspectives on communist sexual morality and its relationship to the then dominant bourgeois and Christian model.